1988
DOI: 10.1111/j.1476-5381.1988.tb11677.x
|View full text |Cite
|
Sign up to set email alerts
|

The contractile activities of lipoxin A4 and lipoxin B4 for guinea‐pig airway tissues

Abstract: The isometric contractile activities of lipoxin A4 (LxA4) and lipoxin B4 (LxB4) were evaluated on guinea‐pig lung tissue over the concentration range, 10−8 to 10−5 m. LxA4 contracted guinea‐pig lung parenchymal strips; the concentration eliciting 50% maximum histamine response was 3 × 10−6 m. LxA4 did not contract tracheal spirals. The LxA4 dose‐response curve was parallel to that of leukotriene D4 (LTD4) with LxA4 being approximately 10,000 fold less potent than LTD4. The time course of the contraction elicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

1991
1991
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…This result suggests that when melittin is applied to the trachea, lipoxygenase products are generated in trachealis smooth muscle and thereby induce contraction. It is conceivable that peptide leukotrienes may mediate the melittin response since they are more potent bronchoconstrictors in man (Dahlen et al, 1980;Jones et al, 1982) and guinea-pigs (Drazen et al, 1980;Weichman et al, 1982) than other lipoxygenase products such as LTB4, which induce cyclooxygenase-dependent contraction (Lawson et al, 1986) and lipoxins, which are inactive in tracheal preparations (Jacques et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…This result suggests that when melittin is applied to the trachea, lipoxygenase products are generated in trachealis smooth muscle and thereby induce contraction. It is conceivable that peptide leukotrienes may mediate the melittin response since they are more potent bronchoconstrictors in man (Dahlen et al, 1980;Jones et al, 1982) and guinea-pigs (Drazen et al, 1980;Weichman et al, 1982) than other lipoxygenase products such as LTB4, which induce cyclooxygenase-dependent contraction (Lawson et al, 1986) and lipoxins, which are inactive in tracheal preparations (Jacques et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Table 2 summarizes some key counter-regulatory lipoxin actions on acute inflammatory reactions for both in vitro and in vivo settings that had been described up to ~ 1998. hamster cheek pouch microcirculation LXA4 (10 -6 M) arteriolar dilation without vascular permeability or leukocyte adherence [10] systemic and renal hemodynamics in rats LXA4 (~ 10 -8 M) arteriolar dilation, selective fall in afferent arteriolar resistance, glomerular hyperperfusion, hypertension and hyperfiltration [11] cerebral arteries of neonate pigs LXA4 and LXB4 (0.1 to 10 ng/ml) dilation, not prostanoid-dependent [12] mesenteric circulation in conscious rats LXA4 and LXB4 (1-100 g/kg/min) i.v. administration constricts mesenteric vessels (transient) [13] aortic smooth muscle from guinea pig, rat and rabbit LXA4 and LXB4 (0.5 to 1.1 x 10 -6 M) promote endothelium-dependent relaxation [14] guinea pig lung strips LXA4 (10 -8 M) depresses LTC4-induced contraction in vitro [15] human pulmonary muscle LXA4 (> 10 -6 M) blocks LTC4-induced contraction in vivo [16] human pulmonary artery LXA4 reverses contractile response to PGF2 and endothelin [17] rat renal hemodynamics LXA4 (1 g/kg/min) antagonises in vivo actions of LTD4 on glomerular filtration rate [18] The In 1998 Gronert and colleagues made the key observation that LXA 4 and synthetic LXA 4 analogs can attenuate tumor necrosis factor alpha (TNF )-induced interleukin-8 (IL-8) release from human enterocytes and epithelial cell lines [30]. Similarly, pathogen-induced epithelial cell IL-8 release was also attenuated by LXA 4 [31].…”
Section: Fig (6) Lipoxins As Counter-regulatory Eicosanoidsmentioning
confidence: 99%
“…In this section we will briefly review some salient data that support this concept from the perspective of lipoxin effects on vascular and inflammatory responses. Table 1 summarizes data obtained for LXA 4 and LXB 4 in various vascular preparations, either when given alone or in conjunction with other vasoactive substances, such as LTC 4 , LTD 4 and PGF 2a [10][11][12][13][14][15][16][17][18]. As compared to thromboxanes, prostaglandins, prostacyclins and the leukotrienes, it has generally been found that LXA 4 and LXB 4 have rather weak direct vasoactivity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In accordance, LXA4, (6S)LXA4 and the all-trans isomers of LXA4 and B4 were formed after addition of 15-H(P)ETE to purified 5-LO from porcine leukocytes [I I]. An alternative pathway for lipoxin synthesis was suggested by Kuhn et al, who demonstrated that LXB4 can be formed by pure reticulocyte lipoxygenase via sequential triple lipoxygenation of arachidonic acid, with (5S,15S)-5,15-dihydroxyeicosatetraenoic acid (5, as an intermediate [12]. This route of formation was further indicated by the finding that porcine leukocyte 12-LO mediated the production of LXB4 from 5,15-diH(P)ETE, suggesting that the enzyme possessed 14R-oxygenation-activity [I 31.…”
mentioning
confidence: 99%